Virtually home: Feasibility study and pilot randomised controlled trial of a virtual reality intervention to support patient discharge after stroke. (April 2018) - Threapleton, Kate; Newberry, Karen; Sutton, Greg; Worthington, Esme; Drummond, Avril
Introduction: Virtual reality has the potential to assist occupational therapists in preparing patients for discharge by facilitating discussions and providing education about relevant practical issues and safety concerns. This study aimed to explore the feasibility of using a virtual reality intervention to support patient discharge after stroke and pilot its use. Method: Practical aspects of delivering a virtual reality intervention prior to discharge were explored by means of a non-randomised feasibility study and a subsequent pilot randomised controlled trial. Factors considered included eligibility, recruitment, intervention delivery, attrition and suitability of outcome measures. Outcome measures included standardised assessments of stroke severity, mobility, health-related quality of life, functional ability, satisfaction with services and concerns about falling. Results: Thirty-three participants were recruited in total: 17 to the feasibility study and 16 to the pilot trial. At 1-month follow-up, 14 participants (82%) were re-assessed in the feasibility study and 12 (75%) in the pilot trial. The main difficulties encountered related to recruitment, particularly regarding post-stroke cognitive impairments, the presence of mild deficits or illness. Conclusion: It was feasible to recruit and retain participants, deliver the intervention and collect outcome measures, despite slow recruitment rates. These findings could inform the design of a definitive trial.